The Impact of Australian and European Foreign Aid on Public Infrastructure Development in Papua New Guinea - Sukma Ayu Putri Ariningtyas; Humaira Faiz (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
Australia has been a major donor in the development process in Papua New Guinea (PNG) since the beginning of independence. Along with Australia, many other donors including Japan, Europe and China. Multilateral institutions such as the World Bank, IMF, and UNDP have also supported the funding of central projects in PNG. Foreign aid is needed to fulfil public infrastructure facilities, especially for poor and new countries. This research contribute to explain about Australia and the European Union have been donor partners for PNG mainly in primary sector funding, such as clean water provision, health services, prevention of gender-based violence, human rights enforcement, providing bureaucratic reform, forest preservation, and other sectors. This research explains the support provided by foreign aid from Australia and Europe for PNG's development. Uses qualitative research based on literature studies from previous research related to the history of providing foreign aid to PNG. Various forms of aid have been utilized by PNG including technical assistance, projects, and grants. As a country that still relies on the agricultural sector and mining management, PNG relies on support from various donors. This support has a significant impact on human development, public infrastructure and the achievement of global development goals. Therefore, PNG was able to build primary infrastructure from foreign aid while simultaneously increasing the country's institutional capacity through strengthening democracy, enforcing human rights, preventing gender-based violence, and bureaucratic reform.Â Australia telah menjadi donor utama dalam proses pembangunan di Papua Nugini (PNG) sejak awal kemerdekaan. Selain Australia, banyak pemberi donor lainnya yaitu Jepang, Eropa, dan China. Lembaga multilateral seperti World Bank, IMF, UNDP juga menjadi penyokong begitu banyak pendanaan dari proyek-proyek sentral di PNG. Bantuan luar negeri memang sangat dibutuhkan guna pemenuhan sarana infrastruktur publik, khususnya bagi negara miskin dan baru merdeka. Penelitian ini berkontribusi dalam pembahasan tentang pentingnya dukungan bantuan luar negeri dari Australia dan Eropa bagi upaya-upaya pembangunan dan kesejahteraan PNG. Metode dalam penelitian ini menggunakan riset kualitatif berbasis studi literatur dari riset pendahulu yang berkaitan dengan topik sejarah pemberian bantuan luar negeri untuk PNG. Berbagai bentuk bantuan telah dimanfaatkan oleh PNG meliputi bantuan teknis, proyek, maupun hibah. Sebagai negara yang masih mengandalkan sektor pertanian dan pengelolaan pertambangan sebagai SDA andalan, PNG masih terus membutuhkan dukungan dari berbagai pihak donor. Dukungan ini sangat signifikan dampaknya bagi pembangunan manusia, infrstruktur publik mapun pencapaian tujuan pembangunan global. Hasilnya, PNG mampu membangun infrastruktur primer dari dana bantuan luar negeri sekaligus meningkatkan kapasitas kelembagaan negara melalui penguatan demokrasi, penegakan HAM, pencegahan kekerasan berbasis gender, reformasi birokrasi dan sebagainya